2022
DOI: 10.3389/fsoc.2022.966878
|View full text |Cite
|
Sign up to set email alerts
|

Savvy and woke: Gender, digital profile, social media competence, and political participation in gender issues among young Filipino netizens

Abstract: Social media has become a viable platform for political participation in issues related to gender, especially among the youth. Evidence suggests that gender and sexual identities, digital access, and skills foster political participation in social media. This study sought to determine the predictive relationship of gender, digital profile, and social media competence with social media political participation in gender issues (SMPP-GI) among young Filipino netizens through the lenses of social identity theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“… Shafer et al (2022) suggested that social media was used as a form of surveillance for their romantic partners. Emerging adults also made use of social media for political participation and civic engagement during the pandemic ( Dayrit et al, 2022 ; Yazdani et al, 2022 ). In the Philippines, a qualitative study indicated that emerging adult college students use social media to maintain their ties with peers during pandemic-induced community quarantine.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Shafer et al (2022) suggested that social media was used as a form of surveillance for their romantic partners. Emerging adults also made use of social media for political participation and civic engagement during the pandemic ( Dayrit et al, 2022 ; Yazdani et al, 2022 ). In the Philippines, a qualitative study indicated that emerging adult college students use social media to maintain their ties with peers during pandemic-induced community quarantine.…”
Section: Literature Reviewmentioning
confidence: 99%